Persepsi Orangtua Pemulung Terhadap Penyelenggaraan Sekolah Impian di Kota Makassar - Syamsul Bakhri Gaffar; Latang Latang; Rahmawati Syam (Seminar Nasional LP2M UNM, 2022)
Abstrak. The problem in this study is how parents perceive the implementation of Dream School in Makassar City. This study aims to determine the parents perceptions of scavengers on the implementation of Dream School in Makassar City. The approach use is a quantitative approach to the type of survey research. The population of this research is parents of scavengers who have early childhood who are involved in Dream School in Makssar City. Data collection techniques were carried out by using questionnaires on parents perception of scavengers on the implementation of Dream School, and documentation techniques by recording and documenting data related to Dream Schools in Makassar City. The data analysis technique used is descriptive statistical by using percentage. The results showed that the parents perception of waste collectors on the implementation of Dream School in Makassar City was very helpful for parents in educating their children, reducing anxiety obout the future of children, parents having plenty of time to do activities both as scavengers an as housewives. Kata Kunci: Perception, Parents of scavengers, Dream School